Da casa ao mangue: abordagem sócio-ecológica do processo de trabalho das marisqueiras do estuário do Rio Paraíba-PB - Silva, Emanuel Luiz Pereira da (2011)
This dissertation deals with the contemporary intricacies infers the processing and handling of ecological harvesting of Pickers Seafood by the cities of Bayeux, and João Pessoa and Cabedelo in Paraiba depending on the environment where shellfish grow. This study was undertaken to analyze the relationship of socio-ecological process and organization of work that occur in the pick up process and marketing of shellfish seafood by the riverside communities of the estuary of River Paraíba. Among the qualitative methods include: life history, free interviews, semi-structured, guided tours and direct observation, the data were analyzed by interpreting the speech of the interviewees, based on the model of the integration of the various individual skills. The knowledge that these women have about the distribution of resources and its ecology, and environmental perception, constitutes a valuable tool in that it is enough to be incorporated in both plans of socio-economic studies and in management, conservation and sustainable use of local fauna.